The spatial spillover effect of transportation networks on ecological footprint - Tianyu Lv (Elsevier, 2021)
In the context of rapid urbanization and regional development worldwide, the efficient and rational spatial distribution of transportation networks is vitally important in achieving sustainable development. In this study, we used an adjusted three-dimensional ecological footprint model (EF3D) to assess regional sustainable development. We explored the driving factors and spatial influence of transportation networks on the EF3D in the urban agglomerations in the middle reaches of the Yangtze River (UAMRYR), China, in 2010 and 2017, integrating the STIRPAT model and spatial econometric model alongside the transportation network in the research framework. The results show that the EF3D has been reduced by 1.46% from 2010 to 2017. Although the overall level of sustainable development in UAMRYR has improved, 94.69% of the county units were still in ecological overshoot in 2017. In addition, population density, GDP per capita and the proportion of non-tertiary industries had positive local influences on EF3D. At the county level, EF3D had positive spatial autocorrelation, and the spatial spillover effect of EF3D was confirmed through the transportation network, indicating that the spatial influence of the transportation network was an important factor in explaining EF3D. Population density and GDP per capita had negative and positive indirect spatial effects, respectively. In the future, the function of transportation systems should be improved to transfer the population pressure of cities and increase natural capital flexibility to reduce the EF and ultimately achieve balanced development.